Efficiency using budgetary funds for stimulation of inntovation process in manufacturing industry - N. D. Anisimkova (Вестник СибАДИ)
The paper dwells on the problems of innovation development of manufacturing industry connected with the current economic crisis and budgetary constraints in Russia. The budget policy of developing industrial and innovationeconomics in Russia is analyzed. There are considered the main government programs for 2002 - 2017 years and their efficiency is revealed.